2005
DOI: 10.1016/j.ydbio.2005.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The homeodomain protein Meis1 is essential for definitive hematopoiesis and vascular patterning in the mouse embryo

Abstract: Homeodomain proteins of the Meis subfamily are expressed dynamically in several organs during embryogenesis and exert potent regulatory activity through their interaction with Hox proteins and other transcription factors. Here we show that Meis1 is expressed in the hematopoietic stem cell (HSC) compartment in the fetal liver, and in the primary sites of definitive hematopoiesis, including the aorta-gonad-mesonephros (AGM) mesenchyme, the hemogenic embryonic arterial endothelium, and hematopoietic clusters with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
220
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(231 citation statements)
references
References 67 publications
11
220
0
Order By: Relevance
“…8 The distribution of ectopic blood foci matches the pattern of nascent lymphatic vessels at E12.5 and E13.5 (Figure 1a through 1d), 1 and analysis of endothelial and lymphendothelial markers identified the ectopic blood foci as the recently formed lymphatic sacs, which were filled with erythrocytes ( Figure 1e through 1g and 1i through 1k). Meis1 is not expressed in blood vascular endothelial cells 8 or lymphatic endothelium (Figure 1h and 1i), suggesting a nonautonomous involvement of nonvascular cells.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…8 The distribution of ectopic blood foci matches the pattern of nascent lymphatic vessels at E12.5 and E13.5 (Figure 1a through 1d), 1 and analysis of endothelial and lymphendothelial markers identified the ectopic blood foci as the recently formed lymphatic sacs, which were filled with erythrocytes ( Figure 1e through 1g and 1i through 1k). Meis1 is not expressed in blood vascular endothelial cells 8 or lymphatic endothelium (Figure 1h and 1i), suggesting a nonautonomous involvement of nonvascular cells.…”
Section: Resultssupporting
confidence: 56%
“…Meis1 (myeloid ecotropic viral integration site 1) encodes a homeodomain transcription factor important for definitive hematopoietic stem cell development in the embryo and essential for megakaryocyte lineage development. 8 Here, through characterization of Meis1-deficient mice and targeted ablation of megakaryocytes/platelets, we demonstrate an essential role for platelets in the separation of the blood and lymphatic vasculature.…”
mentioning
confidence: 85%
“…miRNA-221 and -222 also may be more generalized inhibitors of hematopoietic differentiation, because our data (Table 2) predict that they also may regulate myeloid differentiation-associated molecules ( Fig. 2; MEIS1 and ETS1, both proteins shown to be involved in myeloid development (25,26), and FOS, which has been implicated in lymphopoiesis; ref. 27 and unpublished data).…”
Section: Figmentioning
confidence: 87%
“…The Meis genes are more than just markers for the stylopod, as they may themselves play a role in proximal specification; since ectopic expression of these genes can reprogram proximodistal fate at least to some extent (Capdevila et al 1999;Meracader 2000). However, it is important to note that gene inactivation studies have indicated that neither of these genes is essential, at least individually, for normal limb development (Azcoitia et al 2005).…”
Section: Markers For Proximodistal Limb Segmentsmentioning
confidence: 99%